2023
DOI: 10.1111/irv.13106
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory virus circulation during the first year of the COVID‐19 pandemic in the Household Influenza Vaccine Evaluation (HIVE) cohort

Abstract: Background The annual reappearance of respiratory viruses has been recognized for decades. COVID‐19 mitigation measures taken during the pandemic were targeted at respiratory transmission and broadly impacted the burden of acute respiratory illnesses (ARIs). Methods We used the longitudinal Household Influenza Vaccine Evaluation (HIVE) cohort in southeast Michigan to characterize the circulation of respiratory viruses from March 1, 2020, to June 30, 2021, using RT‐PCR o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Finally, as already reported for RSV, it has been suggested that the susceptibility of the host to a given virus may condition circulation of the virus itself and contribute to the modification of the circulation of one or more other respiratory agents. For example, it has been supposed that the large use of the influenza vaccine during the influenza season 2020–2021 may have favored not only the incidence of influenza cases but may have also played a role in the circulation of those viruses that can benefit from the disappearance of influenza viruses [ 79 ]. However, reasons for variations in the circulation of respiratory virus subtypes such as those evidenced for RSV and influenza viruses are difficult to explain.…”
Section: Reasons For Variations In Epidemiology Of Non-sars-cov-2 Vir...mentioning
confidence: 99%
“…Finally, as already reported for RSV, it has been suggested that the susceptibility of the host to a given virus may condition circulation of the virus itself and contribute to the modification of the circulation of one or more other respiratory agents. For example, it has been supposed that the large use of the influenza vaccine during the influenza season 2020–2021 may have favored not only the incidence of influenza cases but may have also played a role in the circulation of those viruses that can benefit from the disappearance of influenza viruses [ 79 ]. However, reasons for variations in the circulation of respiratory virus subtypes such as those evidenced for RSV and influenza viruses are difficult to explain.…”
Section: Reasons For Variations In Epidemiology Of Non-sars-cov-2 Vir...mentioning
confidence: 99%
“…From September 4, 2022, to January 31, 2023, we conducted an analysis across 6 sites in the US to estimate COVID-19 vaccine effectiveness among children and adolescents aged 5 to 17 years by combining data from 3 prospective cohort studies (Pediatric Research Observing Trends and Exposures in COVID-19 Timelines [PROTECT], CASCADIA, and Community Vaccine Effectiveness [CoVE], which is an expansion of the Household Influenza Vaccine Evaluation [HIVE] cohort). [23][24][25] Children and adolescents living in Arizona, Michigan, Oregon, Texas, Utah, and Washington, including individuals from the same household, were eligible for inclusion.…”
Section: Study Populationmentioning
confidence: 99%